Aproximaciones experimentales al establecimiento de la cinética de secado para semillas de quinua (2017)
The effects of moisture content on the physical properties of two varieties of quinoa, 0301 and 0404 were studied through the elaboration of a drying kinetics. The physical properties studied include magnitudes of aerated and packed bulk density, sphericity and dimensions such as length, width and thickness. These physical properties were studied from initial moisture conditions delivered by the supplier 7.0779 % and 13.4517 % for the variety cGC and cTC respectively. It was evidenced that the behavior of the dimensions of the seed a long the drying time is different for each magnitude. The study of these properties with respect to the moisture content is transcendental for the industry in the processes of collection, handling and storage of the same.